Disentangling the resonant Auger spectra of ozone: overlapping core-hole states and core-excited state dynamics. Issue 46 (18th November 2022) - Tenorio, Bruno Nunes Cabral; Møller, Klaus B.; Decleva, Piero; Coriani, Sonia
Abstract : Resonant and non-resonant Auger spectra of ozone are investigated with a multi-reference scheme based on the one-center approximation. The role of core-excited state dynamics and overlapping core-hole states are elucidated. Abstract : We investigate the resonant and non-resonant Auger spectra of ozone with a newly implemented multi-reference protocol based on the one-center approximation [Tenorio et al., J. Chem. Theory Comput. 2022, 18, 4387–4407]. The results of our calculations are compared to existing experimental data, where we elucidate the resonant Auger spectrum measured at 530.8 and 536.7 eV, that correspond to the 1sOT → π*(2b1 ) and 1sOT → σ*(7a1 ) resonances, and at 542.3 eV, which lies near the 1sOC → σ *(7a1 ) excited state and above the 1sOT −1 ionization threshold. Using molecular dynamics simulations, we demonstrate the relevance of few-femtoseconds nuclear dynamics in the resonant Auger spectrum of ozone following the 1sOT → π*(2b1 ) core-excitation.